Upah Sistem Bagi Hasil Dan Penyerapan Tenaga Kerja - Haryo Kuncoro (Economic Journal of Emerging Markets, 2002)
Reducing unemployment and then creating productive employment are two of the greatest obstacles in most developing countries. Achieving the two programs, however, faces a dilemma. In one hand, creating employment widely leads to decline labor’s compensation. On the other hand, increasing labor’s compensations imply that employers would alter their production techniques into capital intensives (i.e. lay off their workers). This paper tests the hypothesis that workers whose compensation packages contain a profit sharing component are less susceptible to lay off in the face of negative shocks to product demand than are workers paid a fixed, time-based wage. The theory is tested on macroeconomic data, especially in the two selected manufacturing industries in Indonesia. The estimation result shows that profit-sharing meet the theoretical requirements for stabilizing employment. It means that profit sharing could be considered as a means to combat unemployment.